2011
DOI: 10.1101/gr.125146.111
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of evolution following whole genome versus tandem duplication events inPopulus

Abstract: Comparative analysis of multiple angiosperm genomes has implicated gene duplication in the expansion and diversification of many gene families. However, empirical data and theory suggest that whole-genome and small-scale duplication events differ with respect to the types of genes preserved as duplicate pairs. We compared gene duplicates resulting from a recent whole genome duplication to a set of tandemly duplicated genes in the model forest tree Populus trichocarpa. We used a combination of microarray expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
147
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(166 citation statements)
references
References 72 publications
(90 reference statements)
17
147
1
1
Order By: Relevance
“…Adaptations possibly related to the arborescent habit were visible in convergent tandem expansions shared by B. pendula and Populus trichocarpa, including genes associated with fungal pathogen defense, cell wall biogenesis, and cellulose synthase activity (Supplementary Tables 11 and 12). Through evolutionary information stored within single genomes, these results suggest that whereas polyploid duplicates tend to diversify core processes in developmental and physiological regulation, tandem duplicates enhance the diversity of a plant's environmental response capacity, which is in concurrence with previous studies 15,17,18 .…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Adaptations possibly related to the arborescent habit were visible in convergent tandem expansions shared by B. pendula and Populus trichocarpa, including genes associated with fungal pathogen defense, cell wall biogenesis, and cellulose synthase activity (Supplementary Tables 11 and 12). Through evolutionary information stored within single genomes, these results suggest that whereas polyploid duplicates tend to diversify core processes in developmental and physiological regulation, tandem duplicates enhance the diversity of a plant's environmental response capacity, which is in concurrence with previous studies 15,17,18 .…”
supporting
confidence: 86%
“…Genome sequencing and population genomic analyses provide insights into the adaptive landscape of silver birch after independent WGDs, as we obtained highly similar functional enrichments in corresponding analyses of the Arabidopsis thaliana and poplar genomes 15 (Supplementary Table 12), which have experienced their own lineage-specific WGDs 5,16 since diverging from a common ancestor with birch. In contrast to biased retention of modular TF function after WGDs, tandemly duplicated genes in these three species 15 were enriched for environmental responses and secondary metabolism, which, although distinctive by species, were also significantly overlapping (P < 2.2 × 10 −16 , Fisher's test; Supplementary Note, Supplementary Fig.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In total, 15 GO-slim labels showed enrichment. These included many genes in categories such as regulation of biological process, growth, and ribosome and signal transduction, typical for regulatory and developmental genes that are often highly connected and present in macromolecular complexes and/or stoichiometric pathways, which have frequently been observed before to be overrepresented and retained long after the WGD event itself in several angiosperm and metazoan genomes (Hakes et al, 2007;Freeling, 2009;Bekaert et al, 2011;Rodgers-Melnick et al, 2012). This is confirmed by the more extensive list of full GO terms that are found to be overrepresented in the homoeologs, where again many genes with roles that can be associated with plant regulation and development are found (Supplemental Data Set 1).…”
Section: Regulatory and Developmental Genes Are Overrepresented In Thmentioning
confidence: 99%
“…The evolutionary properties of WGD duplicated genes have been explored in diverse lineages, such as yeast (Saccharomyces cerevisiae), Arabidopsis, poplar, Xenopus laevis, Paramecium tetraurelia, and Tetraodon nigroviridis (Papp et al, 2003;Blanc and Wolfe, 2004;Aury et al, 2006;Brunet et al, 2006;Sémon and Wolfe, 2008;Rodgers-Melnick et al, 2012). In addition to the discovery that WGD duplicated genes are functionally biased (Blanc and Wolfe, 2004;Seoighe and Gehring, 2004;Aury et al, 2006;Freeling, 2008;Wu et al, 2008;Schnable et al, 2009), several gene features were identified to associate with their retention probability, such as gene complexity (He and Zhang, 2005), gene length , essentiality (He and Zhang, 2006), expression level (Seoighe and Wolfe, 1999), evolutionary rates , number of protein interactions (Guan et al, 2007;Hakes et al, 2007), functional category (Blanc and Wolfe, 2004), alternative splicing status (Kopelman et al, 2005), protein structure (Papp et al, 2003;Liang et al, 2008), position in the protein-protein interaction network Wu and Qi, 2010), and number of phosphorylation sites (Amoutzias et al, 2010).…”
mentioning
confidence: 99%